1998
DOI: 10.3109/10425179809072188
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of a Mouse Gene with Homology to the Duffy-Antigen Receptor for Chemokines

Abstract: The Duffy antigen receptor for chemokines (DARC) is a receptor for both CXC and CC chemokines. We have cloned a mouse gene with a predicted amino acid sequence homology of approximately 63% to human DARC and localized this gene to mouse chromosome 1 between the Xmv41 and D1Mit166 loci. We further demonstrated that, like the human gene, the mouse gene exhibits a single intron of 462 bp which interrupts the open reading frame between the codons for the seventh and eighth amino acid residues. Northern blot analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We suspect that regulator DARC may also participate angiogenesis in breast cancer. Although some studies had shown that DARC is expressed in several kinds of tumors, including erythroleukemia Inhibition of breast cancer growth and metastasis by DARC J Wang et al , glioblastoma (Desbaillets et al, 1997) and hemangiosarcomas (Tang et al, 1998), the function of DARC in tumors remains unknown. In order to investigate the effects and the mechanisms of DARC in breast tumor, we established DARC overexpressing MDA-MB-435HM and MDA-MB-231 cell lines by stable transfection.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that regulator DARC may also participate angiogenesis in breast cancer. Although some studies had shown that DARC is expressed in several kinds of tumors, including erythroleukemia Inhibition of breast cancer growth and metastasis by DARC J Wang et al , glioblastoma (Desbaillets et al, 1997) and hemangiosarcomas (Tang et al, 1998), the function of DARC in tumors remains unknown. In order to investigate the effects and the mechanisms of DARC in breast tumor, we established DARC overexpressing MDA-MB-435HM and MDA-MB-231 cell lines by stable transfection.…”
Section: Discussionmentioning
confidence: 99%
“…XCR1 is the receptor for XCL1 (lymphotactin) and CX3CR1 for CX3CL1 (fractalkine) (see ref [19] for review). A chemokine-binding protein, also known as the Duffy antigen receptor for chemokines, has been shown to bind promiscuously to CXC and CC chemokines [20]. In addition, other 7TM GPCR, encoded by herpes-and poxviruses, have been identified [21,22].…”
Section: Chemokines and Their Receptorsmentioning
confidence: 99%
“…It was reported that DARC was expressed in some tumors including erythroleukemia, glioblastoma, and hemangiosarcomas [8][9][10], and that the microvessel density (MVD) was commonly considered a consistent indicator of angiogenesis in human cancer [11]. In tissue sections, angiogenesis could be highlighted immunohistochemically using antibodies against vascular endothelium such as CD34, factor VIIIrelated antigen, or CD31 [12].…”
Section: Introductionmentioning
confidence: 99%